3D conductive iron fluoride (III) cathode with high loading for lithium-ion batteries. (2nd February 2023) - Jiang, Qinting; Li, Xifei; Li, Jun; Wang, Jingjing; Cao, Guiqiang; Duan, Ruixian; Zhang, Zheng; Cao, Yanyan; Li, Wenbin; Hu, Junhua
Abstract: The conversion-typed FeF3 cathode, while having high theoretical capacities, suffers seriously from low intrinsic conductivity, sluggish reaction kinetics, and side reactions in lithium ion batteries (LIBs). In particular, composites with high loading FeF3 show poor cycling performance. This paper proposes an effective strategy for nanoconfinement in the 3D conductive matrix to address the aforementioned challenges of FeF3 . FeF3 nanoparticles are only 10–50 nm due to being nanoconfined. The loading of the composite is as high as 81.89%, which is the highest compared to other composites reported previously. The prepared iron fluoride-carbon nanofiber composites offer high reversible capacities of as high as 313 mAh g −1 at 0.1 C. Moreover, it shows an enhanced cycle stability of 88.4% after 100 cycles at 1 C. The improved electrochemical performance is attributed to the 3D conductive network as well as the nanoconfinement of FeF3, which achieve a good capacitance-controlled process by accelerating electron transport while shortening the ion transport path. It is believed that this work provides an efficacious strategy to enhance the electrochemical performance of conversion-typed metal fluoride cathodes for LIBs.